English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

Given that f(x) = 3x + 4 and g(x) = -x^2, find the following.

1. 2f(5)
A. 42
B. 72
C. 38
D. 54

2. f(2) * g(2)
A. -40
B. 40
C. 26
D. -26

Thanks in Advanced =)

2007-03-09 03:26:17 · 13 answers · asked by Anonymous in Science & Mathematics Mathematics

13 answers

1. C
2. A

2007-03-09 04:26:41 · answer #1 · answered by Alias 2 · 0 0

1. First you find f(5). Substituting 5 for x, f(5)=3(5)+4=19.
Then you find 2f(5), which means 2 multiplied by f(5) so
2f(5)=2 times 19
= 38

2.Do f(2) and g(2) separately first if you are not too confident on these. f(2)=3(2)+4=10 g(2)=2²
Therefore f(2)*g(2)=10*4
=40

Hope This Helps =)

2007-03-09 11:37:06 · answer #2 · answered by Forsaken 2 · 0 1

IF f(x)=3x+4 THEN 2f(5) =

SUBSTITUTE 5 IN THE PLACE OF x AND CALCULATE THEN MULTIPLY WITH 2 GIVES THE ANSWER..
f(5)=3*5+4=19
2f(x)=2f(5)=19*2=38... SO ANSWER IS " C "
2) SIMILARLY f(2)*g(2)=(3*2+4)*(2^2)=10*4=40
SO THE ANSWER IS B

2007-03-09 11:37:18 · answer #3 · answered by JEGADEV 1 · 0 1

HI,
the answer for the first one will be derived thus

u substitute 5 in place of x in the first equation
hence the first equation would look like this

f(5)=((3*5)+4)
which is 19

But the question asks for 2f(5)

hence we have to multiply the answer by 2
cos f(5)=19 hence 2f(5)=38

so the answer for the first question is 38 (answer C)



Question 2

first split this question into 2 parts
lets look at f(2) first

u substitute 2 in place of x
you will have
f(2)=((3*2)+4)
f(2)=10

now lets look at g(2)
u substitute 2 in the place of x (in the 2nd equation)
you will have

g(2)=-2^2 (i assume its (-X^2)
= 4

hence f(2)*g(2) = 10*4
=40

so the answer for this is 40 (part b)

hope this helps:)

2007-03-09 11:39:57 · answer #4 · answered by vandhiyathevan 3 · 0 1

1. 2*19 = C. 38

2. 10 * -4 = A -40

2007-03-09 11:33:40 · answer #5 · answered by le_papillon_vert 2 · 0 0

1. 2f(5) = 2(3(5) +4) = 2(15+4) = 2(19) = 38

2. f(2) * g(2)
= [3(2) +4] * [-(2)^2]
= [6+4]*[-4]
=-40

2007-03-09 11:33:25 · answer #6 · answered by ironduke8159 7 · 0 0

1) 2* f(5)

= 2 * (3*5 +4)

= 2* (15 +4)

= 2* 19

= 38 = C

2 ) = (3x +4) * (-x^2)

= (3*2 +4 ) * (-2^2)

= (6 +4) * (4) or -4 (it depends if it is -(x^2) or (-x^2)

= (10*4)= 40 or -40.

2007-03-09 11:34:16 · answer #7 · answered by The exclamation mark 6 · 0 0

1) C: 2(3x5 +4) = 38

2) A: (3x2+4)(-2^2) = -40

2007-03-09 11:34:05 · answer #8 · answered by Mark M 2 · 0 0

2f(5) = 2(3*5 + 4) = 2(19) = 38
f(2)*g(2) = (3*2 + 4)*(-(2²)) = (10)*(-4) = -40

That was pretty easy, wasn't it?

Doug

2007-03-09 11:33:47 · answer #9 · answered by doug_donaghue 7 · 0 0

2f(2) = 2(3(5)+4)= 38 (B)

f(2) *G(2) = (2*3+4 ) * (4) = 40 (B)

2007-03-09 11:35:42 · answer #10 · answered by Brian D 5 · 0 1

1. 2f(5)
C. 38


2. f(2) * g(2)

B. 40

2007-03-09 11:31:56 · answer #11 · answered by aeiou 7 · 0 1

fedest.com, questions and answers